2020
DOI: 10.1002/chem.202001193
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis of Short DNA Fragments

Abstract: We report the general and rapid synthesis of short DNA fragments of controllable sequence and length using multi-step, one-pot mechanochemical reactions, without bulk solvent or the need to isolate intermediates. We demonstrate, for the first time, the multi-step ball milling synthesis of DNA dimers and trimers via phosphoramidite and H-phosphonate chemistries. The use of mechanochemistry allowed for coupling of phosphoramidite monomers to the 5'-hydroxyl group of nucleosides, iodine/water oxidation of the res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…The experiments performed in figure 5 have wider ramifications for mechanochemical results reported throughout the literature. Researchers will sometimes analyse the outcomes of ball-milling reactions by directly dissolving mixtures in deuterated solvents for analysis by NMR, or by dissolving the reaction mixture in solvents before purifying the desired compound by liquid–liquid extraction and column chromatography [ 17 ]. Phosphoramidites are highly reactive and there is a possibility that with ‘solventless’ reaction conditions, additional or even unwanted reactions occur upon addition of solvent to the milling vessel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments performed in figure 5 have wider ramifications for mechanochemical results reported throughout the literature. Researchers will sometimes analyse the outcomes of ball-milling reactions by directly dissolving mixtures in deuterated solvents for analysis by NMR, or by dissolving the reaction mixture in solvents before purifying the desired compound by liquid–liquid extraction and column chromatography [ 17 ]. Phosphoramidites are highly reactive and there is a possibility that with ‘solventless’ reaction conditions, additional or even unwanted reactions occur upon addition of solvent to the milling vessel.…”
Section: Resultsmentioning
confidence: 99%
“…It has also enabled reactions involving hydrolytically sensitive chlorophosphoramidites and phosphorodiamidites [14][15][16]. More recently, the mechanochemical synthesis of dinucleotides was reported by Thorpe et al [17] in which the phosphite triester bonds were generated from phosphoramidites upon activation with 5-(ethylthio)-1H-tetrazole under solventless conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, several problems remain with this approach. These include the need for large excesses of reagents to achieve satisfactory coupling efficiencies, the use of expensive non-reusable polymeric supports, and finally the use of large volumes of solvents 1,2 for solubilisation of the non-immobilised reagents and washing the solid support following reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The deprotected ionic liquid-bound nucleoside 4 was dissolved in a minimal volume of acetone and added to a ball-milling vessel. Following evaporation of the acetone, the milling vessel was placed under high vacuum at 70 o C overnight to facilitate removal of any residual acetone and water 1. H NMR confirmed that depyrimidation again did not occur after 4 was subjected to these conditions(Fig.…”
mentioning
confidence: 98%
“…[41b] In the prebiotic context, ball milling has been applied for synthesizing relevant building blocks such as a-aminonitriles [43,44] and monosaccharides [45,46] under plausible early Earth conditions. Furthermore, chemical syntheses of nucleotides, [47] DNA fragments, [48] and lipid derivatives [49] have been developed in ball mills, and solid-state approaches have led to DNA-specific recognition and self-assembly of model nucleobases. [50] Additionally, the use of other setups such as flow chemistry photoreactors has proven helpful to recreate prebiotic environments for chemical transformations.…”
mentioning
confidence: 99%